TINJAUAN YURIDIS PEMBENTUKAN PANITIA KHUSUS SEBAGAI ALAT KELENGKAPAN DEWAN PERWAKILAN RAKYAT DAERAH - Sugiyanto, Sugiyanto; Cornelis, Vieta Imelda; Hamdani, Fathul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study provides a juridical review of the formation of Special Committees (Pansus) as an integral part of the Regional House of Representatives (DPRD) in Indonesia. Using a normative legal research approach, this study analyzes the legal basis, mechanisms, and practical implications of the Pansus's existence. The findings indicate that the Pansus is a legitimate and vital ad hoc instrument, created to address specific issues that require focus and efficiency. Its formation is formally regulated through the DPRD Plenary Meeting's Decree and is based on relevant legislation, including Law Number 23 of 2014 and Government Regulation Number 12 of 2018. This process ensures the Pansus has strong legitimacy, accountability, and representation. The Pansus enables the DPRD to carry out its legislative and oversight functions more thoroughly, expedites decision-making, and enhances local government transparency. This study concludes that the Pansus is not merely a formal structure but a crucial mechanism for making the DPRD more responsive, efficient, and accountable in serving the public's aspirations